STUDI PERKEMBANGAN POLA RUANG KAWASAN MARGONDA RAYA - Kyrana van den Berg; Suryono Herlambang; Parino Rahardjo (Jurusan Arsitektur dan Perencanaan, 2020)
Margonda Raya area is one of the starting points for the development of Depok City (Irsyam, 2017). The area which in 1970 was agricultural land has now become a downtown area. The area is developing quickly into a dense area. New problems arise such as traffic congestion on the other hand large-scale development continues to occur. This indicates an imbalance in development. In addition, the spatial plan for the area was not systematically formed. This study is limited to discussion related to the development of spatial patterns. The study was conducted to determine the shape of spatial pattern development that occurred as well as its alignment with government directives in the existing spatial planning documents. The study was conducted using qualitative and quantitative approaches with comparative descriptive analysis methods. Based on studies conducted, it is identified that current developments have not been fully anticipated in spatial planning. The phenomenon of development that occurs in the Margonda Raya region is very rapid and needs to be anticipated to maintain the balance of development in the future which can affect the quality of life of the people of the city itself. Keywords: Development; Margonda Raya Road; Region; Space Pattern; Spatial AbstrakKawasan Margonda Raya merupakan titik awal perkembangan Kota Depok (Irsyam, 2017). Kawasan yang pada Tahun 1970 merupakan lahan pertanian kini telah menjadi kawasan pusat kota. Kawasan berkembang cepat menjadi kawasan yang padat. Muncul masalah-masalah baru seperti kepadatan lalu lintas disisi lain pembangunan skala besar terus terjadi. Hal ini mengindikasikan adanya ketidakseimbangan pembangunan. Selain itu, rencana tata ruang untuk kawasan tidak dibentuk secara sistematis. Studi ini dibatasi pada pembahasan terkait perkembangan pola ruang. Studi dilakukan untuk mengetahui bentuk perkembangan pola ruang yang terjadi serta keselarasannya dengan arahan pemerintah dalam dokumen rencana tata ruang yang sudah ada. Studi dilakukan menggunakan pendekatan kualitatif dan kuantitatif dengan metode analisis deskriptif komparatif. Berdasarkan studi yang dilakukan, diidentifikasi bahwa perkembangan yang terjadi saat ini belum sepenuhnya diantisipasi dalam rencana tata ruang. Fenomena perkembangan yang terjadi di kawasan Margonda Raya sangat pesat dan perlu diantisipasi untuk menjaga keseimbangan pembangunan yang kedepannya dapat mempengaruhi kualitas hidup masyarakat kota itu sendiri.